Proposing an SLR exploring the assumptions and requirements of the negotiation protocol in MAS - Sumeet Mathur (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The multi-agent system (MAS) community has put noteworthy endeavors in recording design patterns. In spite of the substantial body of work, design patterns for MAS have gotten the consideration they merit, neither in the agent-situated programming community, nor among programming expert. Albeit a large portion of these approaches have just begun investigating the point, there is a looming requirement for building up an exploration guide, just as recognizing logical and technological challenges in this degree. The examination demonstrates that there is an absence of a standard format for reporting design patterns for MAS, which hampers the utilization of patterns by practitioners,) relationship between patterns are ineffectively portrayed, which results in an absence of diagram of the pattern space, patterns for MAS have been utilized for an assortment of use areas, which supports their high potential for practitioners, and arrangements of design patterns for MAS are limited to explicit pattern lists, a progressively all encompassing perspective on the pattern space is absent. From our examination, we plot various guidelines that are vital for future work on design patterns for MAS and their appropriation by and by.